Sapangambei Manoktok Hitei sebagai Basis Kohesi Sosial Masyarakat Multireligius di Pematangsiantar - Vera Astriyani Sinaga (Dimensia: Jurnal Kajian Sosiologi, 2026)
This paper discusses the local value of Sapangambei Manoktok Hitei, understood as a representation of mutual cooperation, solidarity, love, and equality that have been institutionalized in socio-religious life. Through the theory of ethnoreligious nationalism by Christophe Jaffrelot, this value is understood as a form of local nationalism that is the result of a fusion that forms a national identity from traditional roots. In addition, the theory of social solidarity by Emile Durkheim, especially the concept of organic solidarity, is used to interpret social relations in modern heterogeneous societies, where the differentiation of social functions and roles is actually the basis of social cohesion. This paper uses a descriptive qualitative method with an ethnographic approach and literature study to examine the role of philosophy in creating social cohesion, public spirituality, and expressions of local nationalism. Sapangambei Manoktok Hitei becomes a form of collective consciousness that unites differences in a common goal. Thus, this value functions as a symbolic force that unites society, ethnicity, and social interests.